2017
DOI: 10.2754/avb201786030223
|View full text |Cite
|
Sign up to set email alerts
|

The capability of minor quaternary benzophenanthridine alkaloids to inhibit TNF-α secretion and cyclooxygenase activity

Abstract: Quaternary benzophenanthridine alkaloids are known to have a wide range of biological effects, including antimicrobial, antifungal, anti-inflammatory, and antitumour activities. However, only sanguinarine and chelerythrine have been studied intensively. The aim of this study was to evaluate the anti-inflammatory potential of the five minor quaternary benzophenanthridine alkaloids sanguilutine, sanguirubine, chelirubine, chelilutine, and macarpine in vitro and to compare them with more thoroughly studied sangui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…Sanguinarine was found to block tumour necrosis factor-alpha (TNF-α) induced phosphorylation and the degradation of IκBα, an inhibitory protein of nuclear factor (NF)-κB, as well as inhibiting the translocation of the p65 subunit to a nucleus [45]. In this study, the concentrations of TNF-α and IL-4 were decreased in sanguinarine group, it is similar to the reported that sanguinarine has antiinflammatory property in vitro and in vivo, and showed a bility to reduce the secretion of TNF-α [46,47].…”
Section: Sanguinarine Effect On Intestinal Mucosal Morphology and Mucosal Inflammatory Responsesupporting
confidence: 86%
“…Sanguinarine was found to block tumour necrosis factor-alpha (TNF-α) induced phosphorylation and the degradation of IκBα, an inhibitory protein of nuclear factor (NF)-κB, as well as inhibiting the translocation of the p65 subunit to a nucleus [45]. In this study, the concentrations of TNF-α and IL-4 were decreased in sanguinarine group, it is similar to the reported that sanguinarine has antiinflammatory property in vitro and in vivo, and showed a bility to reduce the secretion of TNF-α [46,47].…”
Section: Sanguinarine Effect On Intestinal Mucosal Morphology and Mucosal Inflammatory Responsesupporting
confidence: 86%
“…The main bioactive isoquinoline alkaloids, namely sanguinarine and chelerythrine, are well known for their anti-inflammatory and antimicrobial properties [ 8 , 9 ]. It has generally been found that sanguinarine tends to be more active than chelerythrine with respect to these anti-inflammatory [ 10 , 11 ] and antimicrobial activities [ 7 , 12 ], although this result is not without exception [ 13 ]. Regarding the distribution of sanguinarine and chelerythrine within the plant, both alkaloids are found most abundantly in the capsules (32.08 and 7.36 mg/g dry weight, respectively) followed by the aerial part (4.51 and 2.88 mg/g dry weight, respectively), and at very low concentrations in the seeds (0.07 and 0.02 mg/g dry weight, respectively) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sanguinarine has been shown to cause anti-inflammatory effects in both in vitro and in vivo studies, possibly related to a decrease in the secretion of tumor necrosis factor α (TNF-α) [13,41]. As a quaternary benzo[c] phenanthridine alkaloid, sanguinarine shows an irreversibly inhibitory influence on intestinal aromatic amino acid decarboxylase, thus reducing the production of biogenic amines [42].…”
Section: Discussionmentioning
confidence: 99%
“…Non-antibiotic feed additives such as postbiotics and sanguinarine-based phytobiotic emerged as alternative solutions to AGPs for performance enhancing purposes [11,12] due to their anti-inflammatory activity and capacity to modulate the immune system [13,14]. However, most results originated from experiments under ideal or favorable production conditions.…”
Section: Introductionmentioning
confidence: 99%